Pengelolaan Konten Digital PT Assemblr Teknologi Indonesia - Zahrina Ayu Azizah; Indri Rachmawati (UNISBA Press, 2022)
Abstract. These days, every company uses social media to inform the products or services they offer. PT Assemblr Indonesia also utilizes social media as information media and promotional media. In managing social media, PT Assemblr Teknologi Indonesia itself has stages in managing digital content on social media. Based on the problems that occurred, the author took the title “Digital Content Management of PT Assemblr Technology Indonesia